DAMPAK USAHATANI KARET ALAM TERHADAP SOSIAL EKONOMI MASYARAKAT PEDESAAN DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Nurleli Nurleli; Almasdi Syahza; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abtract: This research was conducted in Teberau Panjang village of Gunung Toar districts Kuantan Singingi regency with a view to analyzing the impact of natural rubber farming on rural social economic communities. Social economic that more study about income level to fulfill household consumption of rubber farmer. Populated community in Teberau Panjang village populated with rubber plantations and making basic livelihoods, then sampled in a porpusive sampling of 100 samples. The sample criteria of the community who own the rubber plamtations either as workers or as landowners. Data analysis technique. Data were analyzed using descriptive analysis. The results showed that the decrease of rubber price caused rubber farmers in Teberau Panjang village to move land from rubber plantation to oil palm plantation community. Rubber plantations in Teberau Panjang village are stll traditionally managed. The management is done simply. After planning is left unattend, only some farmers who after planting rubber seeds doing maintenance, lack of care also cause the quality and productivity of rubber produced low. The impact of farming on the sosio-economic of rural communities in Teberau Panjang village from the results of the study found that the level of income decreased. This is caused by the decline in rubber price and the occurrence of monopsony where the price is determined by toke-toke village so that there is no bargaining among farmers, but it is also caused by the shift of rubber farmers to other communities that is oil palm.Keyword : Natural Rubber Farming, Sosio-Ecomic